Evaluación y conocimientos para prevención del dengue en la ciudadela Brisas del Mar de la ciudad de Machala. - Calba Calba, Carolina Estefanía (2016)
Dengue is a viral disease considered a reemerging entity, the most widespread and prevalent in Ecuador. Whose spread is attributed to expanding geographic distribution of the four dengue viruses and their mosquito vectors the most important of which is Aedes Aegypti, in addition to its ability to adapt to different environmental and social average conditions provided by the man. This research aims to assess the knowledge of dengue prevention that the population of the Brisas del Mar citadel of the city of Machala. An analytical, descriptive study. The Universe was formed by 3,200 people; a sample of 343 of them were taken through the application of a formula that met the inclusion and exclusion criteria that were applied a survey. In this research 97% of the study population has basic knowledge of the disease, 52% do not know the name of the vector for its difficult pronunciation, but if they have knowledge about the mode of transmission of dengue represented by 97%; there is a wrong knowledge on reproduction vector represented by 64%; although most respondents know some form of prevention, but not all practices are shared. As for identifying Dengue symptoms, the study population recognized as major symptoms of fever, headache and muscle pain, as they have presented a case of this disease. Keywords: dengue, knowledge and prevention